PREVALENCE AND DYNAMICS OF FACTORS CAUSING PHYSICAL INACTIVITY IN PREGNANT WOMEN BY AGE (RESULTS OF 3-YEAR EPIDEMIOLOGICAL MONITORING) - Mamasaliev N.S.; Kuzieva G.A.; Asrankulova D.B.; Bakirov G.Z.; Kurbanova R.R. (The Conference Hub, 2025)
Hypertensive disorders in pregnant women are among the most common and significant cardiovascular diseases and syndromes. The significance of this problem is determined by the fact that pregnancy in women with hypertensive conditions is often accompanied by severe health problems and even death of the mother (up to 40% in some countries), high rates of childhood and perinatal morbidity and mortality, and a number of obstetric complications [2].Hypertensive conditions in pregnant women is a concept encompassing various clinical and pathogenetic variants of hypertensive disorders [5].